Congenital leukemia - A diagnostic dilemma - Prakash, KP; Rau, ATK; Bhat, ST; Rau, AR (Indian Journal of Medical and Paediatric Oncology, 2008)
A 6 day old newborn presented with fever, lethargy, poor suck and mild hepatosplenomegaly, features suggestive of sepsis. Septic work up was negative. Peripheral smear revealed hyperleukocytosis, thrombocytopenia and presence of atypical cells. Bone marrow examination revealed increased myeloblasts. Other causes of leukemoid reaction were ruled out and a final diagnosis of congenital leukaemia was made.